The Influence of Lifestyle on Private Employees' Income in Pekanbaru City: Opportunities and Challenges in South Ledge Management for Indonesia - Ritmaratri, Juwita; Khoiruddin, Irvan Ahmat (RISK : Jurnal Riset Bisnis dan Ekonomi, 2025)
South Ledge is located in the South China Sea and is a strategic area with significant natural resource potential. South Ledge management faces great opportunities and complex challenges for Indonesia, involving geopolitical, economic and environmental aspects. This research aims to evaluate the opportunities that Indonesia can take advantage of from managing the South Ledge, including the use of natural resources, potential for economic development, and opportunities to strengthen international cooperation. In addition, this research also identifies key challenges, such as territorial disputes with other countries, environmental impacts from exploration, and limited management capacity. Through qualitative analysis based on literature studies and policy data, this research provides recommendations for sustainable management strategies that can help Indonesia maximize benefits while minimizing risks. The conclusions of this research emphasize the need for strong diplomacy, careful environmental management, and international collaboration to face challenges and take advantage of existing opportunities.